Determining Malay Youth Awareness of Climate Change Education and Ocean Sustainability - Mohd Anis, Arpahdila; Kamaruddin, Norfadilah (Research in Management of Technology and Business, 2024)
The oceans and seas are now under increasing threat from human activities and needing immediate action to protect their health and resilience. Clearly, pollution from human activities, such as industrial effluents and solid waste, continues to pose a threat to marine biodiversity and ecosystem function. Towards these scenario, numbers of initiatives taken by the global world including emphasizes the importance of conserving and using marine resources sustainably for Sustainable Development Goal 14 (Life Below Water). However, despite worldwide initiatives, achieving these objectives remains difficult. Thus, this research examines the importance of educating teenagers on the effects of climate change on ocean sustainability through evaluation of their awareness, attitudes, and behaviors towards environmental conservation activities. This research project aims to introduce a fresh perspective on addressing Malaysia’s pressing ocean sustainability issues. To assess youth awareness and views on ocean sustainability and climate change education, a questionnaire was distributed to youth aged 18 to 25 in Selangor state using voluntary response sample methods. Through iterative design and refinement processes, driven by research insights and professional feedback, the study aspires to enhance youth awareness in ocean sustainability and climate change mitigation, aligning with global priorities for a resilient and equitable future.